2016
DOI: 10.1515/znc-2015-0117
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic effect of Berberis integerrima hydroalcoholic extract on colon cancer development in the 1,2-dimethyl hydrazine rat model

Abstract: The aim of this study was to investigate the efficacy of a Berberis integerrima hydroalcoholic extract as a chemotherapeutic agent in colon carcinogenesis in the rat induced by 1,2-dimethyl hydrazine (DMH). Male Wistar rats were divided into five groups: a negative control group without DMH treatment; a control group injected DMH (20 mg/kg b.w); two groups receiving B. integerrima extract (50 and 100 mg/kg b.w), concomitant with injected DMH, as chemotherapeutic groups; a positive control group receiving 5-flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The increased level of COX-2 exhibited the enhanced production of prostaglandins, which was proven via p-38 MAPK that led to the up-regulation of caspase-3, caspase-8, and caspase-9 or boosted p53 (cell cycle regulator) (Aranganathan et al, 2009;Malayeri et al, 2016). Theanine reduced the levels of p38-MAPK, caspase-3, caspase-8, caspase-9, and p53 and suggesting an anti-inflammatory effect (Figure 8).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The increased level of COX-2 exhibited the enhanced production of prostaglandins, which was proven via p-38 MAPK that led to the up-regulation of caspase-3, caspase-8, and caspase-9 or boosted p53 (cell cycle regulator) (Aranganathan et al, 2009;Malayeri et al, 2016). Theanine reduced the levels of p38-MAPK, caspase-3, caspase-8, caspase-9, and p53 and suggesting an anti-inflammatory effect (Figure 8).…”
Section: Discussionmentioning
confidence: 97%
“…As a result, DMHinduced colorectal cancer showed a reduced level of GST due to its effectual role in detoxification of carcinogen (DMH) metabolites into the liver and boosted the level of GST by theanine, which uses GSH as a substrate. This result might protect the hepatocyte cells and instantaneously reduce colorectal cancer (Hirose et al, 1999;Malayeri et al, 2016;Venkatachalam et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous results demonstrated that medicinal plants with bioactive constituents such as RD essential oil as well as Berberis integerrima and Ferula assafoetida extracts significantly affect oxidative stress-antioxidant parameters and detoxifying enzymes as well as COX-2 gene expression. 9,33,34 There is also evidence indicating hepatoprotective activity of DDW against acetaminophen. 7 Following this, the present study was designed 3), while there was a considerable decrease in the amount of GSH and FRAP (as an important factor in the oxidative stress-antioxidant balance) in comparison with the LAP group (Tables 1 and 2; Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a serious issue of environmental contamination. The compound is currently used in many cancer studies [44,45] because it is a known carcinogen that can cause sporadic forms of colon carcinoma in rats resulting in a reproducible experimental models for pre-clinical screening of test compounds based on its metabolism [46]. It has been reported that the metabolism of dimethyl hydrazine leads to the formation of azoxymethane methylazoxymethanol and methyl diazonium ions, which can cause alkylation of the DNA in the colon mucosa [47].…”
Section: Dimethylhydrazinementioning
confidence: 99%